2013
DOI: 10.1097/mco.0b013e32835e8d9c
|View full text |Cite
|
Sign up to set email alerts
|

Maternal predictors of intrauterine growth restriction

Abstract: Assessing nutritional and environmental factors associated with IUGR, and the molecular mechanisms by which they may have a role in the disease onset, is necessary to provide comprehensive and common guidelines for maternal care and recommended behaviours. Moreover, maternal genetic predispositions and early serum markers may allow a better and more specific monitoring of high risk pregnancies, optimizing the timing of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 75 publications
0
43
0
1
Order By: Relevance
“…6 Environmental factors, nutritional status and diet of the mother also affect fetal development. 7 Alterations in the nutrient supply to the fetus result in nutrient deprivation, causing restricted growth. 7 LBW is a major underlying cause of infant mortality and childhood morbidity.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Environmental factors, nutritional status and diet of the mother also affect fetal development. 7 Alterations in the nutrient supply to the fetus result in nutrient deprivation, causing restricted growth. 7 LBW is a major underlying cause of infant mortality and childhood morbidity.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…7 Alterations in the nutrient supply to the fetus result in nutrient deprivation, causing restricted growth. 7 LBW is a major underlying cause of infant mortality and childhood morbidity. 8 Additionally, there is a clear association between LBW and increased risk for many diseases later in life, such as metabolic syndrome, diabetes mellitus type 2, cardiovascular diseases, hypertension or cancer.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Consumption of a varied and balanced diet, as evidenced for the "New Nordic Diet" [29] or Mediterranean-type diets [30], has been associated with maternal well-being and a favourable pregnancy outcome, and with the offspring's longterm health. It has been shown that macro-and micronutrients are direct regulators of DNA stability and may have an impact on phenotype modifications by influencing epigenetic processes [31,32].…”
Section: Nutrient Supply and Early Programmingmentioning
confidence: 99%
“…Alcohol and tobacco exposure during development affect the expression of genes involved in cell cycle control, apoptosis, and transcriptional regulation, mostly through epigenetic mechanisms [332,333]. Alcohol, tobacco, and caffeine exposure are associated with adverse maternal and child health outcomes [269].…”
Section: Consensus Recommendationsmentioning
confidence: 99%